Severe abrupt (thunderclap) non-traumatic headache at the pediatric emergency department – a retrospective study. (October 2021) - Levinsky, Yoel; Waisman, Yehezkel; Eidlitz-Markus, Tal
Background: Adult abrupt severe non-traumatic headache (thunderclap) is often related to serious underlying etiologies such as subarachnoid hemorrhage. However, data are sparse regarding thunderclap headache in the pediatric population. Objective: The aim of the study was to evaluate the prevalence, characteristics and causes of thunderclap headache in the pediatric and adolescent population, aged 6–18 years, presenting to a pediatric emergency department. Methods: The electronic database of a tertiary care pediatric emergency department was searched for children presenting with acute headache during 2016–2018. Headache severity was defined by pain scales, either a visual analogue scale or by the Faces Pain Scale–Revised. Results: Thunderclap headache was diagnosed in 19/2290 (0.8%) of the included patients, all of them with a pain score of 10/10. All the patients had a benign course. Primary headache was diagnosed in 15/19 (78.9%), six patients had migraine and eight were diagnosed with primary thunderclap headache. Four of the 19 patients were diagnosed with secondary headache: three with infectious causes and one with malignant hypertension. Conclusions: Thunderclap headache is rare among children and adolescents presenting to the emergency department. This headache is generally of a primary origin. Extensive evaluation is still needed to rule out severe diagnosis problems.